2021
DOI: 10.1113/jp282063
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of persistent inward currents are reduced in upper limb motor units of older adults

Abstract: support-information-section).Altamash Hassan is a biomedical engineer who earned his PhD from Northwestern University. During his time at Northwestern, he was mentored by Dr Julius P. A. Dewald, and his research investigates the neural control of movement through analyses of motor unit firing patterns in both healthy and pathological states. Investigating the effects of ageing on motor unit behaviour stemmed from an informal discussion with Dr Gregory Pearcey and provides the foundation for future investigatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 94 publications
(138 reference statements)
2
32
0
Order By: Relevance
“…recruitment and derecruitment) of a higher‐threshold test unit (Gorassini et al., 2002). In the present study, Δ F values are presented as ‘unit‐wise’ averages for all suitable test–control unit pairs, thus reducing the number of Δ F values to one per test unit (Hassan et al., 2021). When individual test units were paired with multiple control units that met inclusion criteria, the average Δ F value was obtained (Hassan et al., 2021; Mesquita et al., 2022; Trajano et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…recruitment and derecruitment) of a higher‐threshold test unit (Gorassini et al., 2002). In the present study, Δ F values are presented as ‘unit‐wise’ averages for all suitable test–control unit pairs, thus reducing the number of Δ F values to one per test unit (Hassan et al., 2021). When individual test units were paired with multiple control units that met inclusion criteria, the average Δ F value was obtained (Hassan et al., 2021; Mesquita et al., 2022; Trajano et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, Δ F values are presented as ‘unit‐wise’ averages for all suitable test–control unit pairs, thus reducing the number of Δ F values to one per test unit (Hassan et al., 2021). When individual test units were paired with multiple control units that met inclusion criteria, the average Δ F value was obtained (Hassan et al., 2021; Mesquita et al., 2022; Trajano et al., 2020). Inclusion criteria for MU pairs were as follows: (i) test MUs were recruited >1 s after control units to enhance the likelihood of full PIC activation; (ii) test MUs ceased firing >1.5 s before control units to reduce the possibility of overestimating Δ F ; and (iii) test units were activated continuously for ≥2 s (Hassan et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study employed a validated and extensively used method of PIC strength estimation in humans (Udina et al, 2010;Hassan et al, 2019Hassan et al, , 2021Trajano et al, 2020;Orssatto et al, 2021bOrssatto et al, , 2021aMesquita et al, 2022) that shows very good repeated-measures reliability, as demonstrated by the high reliability of measurements in the control condition of Experiment 1. However, our findings should not be extrapolated to contraction intensities and motor units with recruitment threshold higher than those used in our study (20% and 30% of peak torques), as discussed previously.…”
Section: Strengths Limitations and Delimitationsmentioning
confidence: 99%
“…Age-related alterations within the nervous system (Manini et al ., 2013; Orssatto et al ., 2018) contribute to the impairments in movement control and force production observed in older individuals (Suetta et al ., 2019). Recent estimates suggest that reduced motor neuronal PIC strength plays a role in these impairments (Hassan et al ., 2021; Orssatto et al ., 2021 a ). However, it is not known whether PIC neuromodulation-inhibition control is also altered with ageing.…”
Section: Introductionmentioning
confidence: 99%